Study and Analysis of “W- Shaped” Meander Line Antenna - N., Sivasankari; K., Abirami; G., Lakshmi Prabha (Journal of Ubiquitous Computing and Communication Technologies, 2025)
This report details the design and analysis of a W-shaped meander line antenna utilizing ANSYS HFSS (High-Frequency Structure Simulator). The antenna is distinguished by its compact design, wide bandwidth, and efficient performance for wireless communication applications. Simulation results, including gain, return loss, efficiency, and directivity, confirm the effectiveness of the W-shaped structure in achieving the desired frequency response. The W-shaped antenna employs a meander line pattern resembling the letter 'W,' which contributes to a reduction in the antenna’s physical size while maintaining the necessary electrical properties. The simulation of this antenna was conducted in ANSYS HFSS v2021. Key results obtained include return loss, radiation pattern, 3D polar plot, sidelobe level, beamwidth, radiated power, and accepted power. This meander line W-shaped antenna is designed for a frequency of 5.2 GHz, demonstrating a return loss of less than -10 dB and a bandwidth of 2 GHz. The antenna achieves a gain of 10 dB at perpendicular angles. A significant advantage of this antenna is its capability to provide a wider bandwidth and a radiation efficiency of 98%.
Keywords: W-shaped Structure; ANSYS HFSS (High-Frequency Structure Simulator); Meander Line Antenna; Wireless Communication; Microstrip Patch Antenna